Biologia populacional, crescimento alométrico e estado de conservação do caranguejo Uca (Uca) maracoani (Latreille, 1802-1803) (Decapoda: Ocypodidae) em um estuário do semiárido brasileiro - Silva, Francisca Mariana Rufino de Oliveira (2015)
Population biology and alometric growth and conservation states of Uca (Uca) maracoani were studied for the first time in a tropical estuary of Northeastern Brazil. A catch-per-unit-effort (CPUE) technique was used to sample the crabs using 60-min sampling periods by one people on a monthly basis during low tide periods from June/2013 to June/2014 in a estuary area of Baixa Grande Beach (4°55’90”S, 37°04’51”W). The following aspects of this population were analyzed: spatial distribution, body size, size-frequency distribution, sex ratio, recruitment of juveniles and handedness. A total of 404 crabs were obtained, of which 315 were males, 87 non-ovigerous females, and two ovigerous females. The U. (U.) maracoani population presented unimodal size frequency distribution (KS=0,08, p > 0.0001). Males (mean±SD: 27,1 ± 5,47 mm CW) were larger than non-ovigerous females (mean±SD: 23,4 ± 4,27 mm CW). The overall sex ratio (3,5:1) differ significantly from the expected 1:1 proportion (2=129,6; p < 0,001). The major cheliped was the right one in 50% of the males (1:0,82; 2 = 3.032; p < 0,001). A total of 294 males and 89 females were used in the alometric study. The specimens were measured at carapace width (CW), the major propodus length (MPL) of males, and abdomen width (AW) of females. In males, the inflection point was at 20.29 mm CW in the relationship between CW and the length of major propodus (MPL), considering the morphological size at the onset of maturity. Based on the relationship between CW and AW, the size at sexual maturity in females was 20.09 mm. Finally, the conservation status of U. (U.) maracoani was analyzed using the method guide proposed by the International Union for Conservation of Nature (IUCN), which is followed by the Brazilian Environmental Agency (ICMBio) to elaborate the red list of Brazilian fauna. According to the guide, was possible characterize the species as Least Concerned (LC) among eleven categories proposed, from Not Evaluated (NE) to Extinct (EX)